PENGELOLAAN PERBATASAN DARAT INDONESIA-MALAYSIA DI KABUPATEN SAMBAS - Nur Syamsiah nur (Jurnal Yustisiabel, 2021)
The purpose of this research is to find a formula to manage the land border area between Indonesia and Malaysia in Sambas Regency. The present border area region issues involve national and state sovereignty as well as mechanism in magement of border areas. There is also an issue that concern the direct interests of border society. The occurrence of these issues as a result of not fully managed. To make land border area between Indonesia and Malaysia in Sambas district better,  need some things that to do such as creating policies regulating to manage of border areas, maximize the role of the central government, provincial government, city government, society and border area management institutions.